Preferences for life-sustaining treatments in advance decisions: a cross-sectional survey of Taiwanese general public - Daniel Fu-Chang Tsai; Yu-Chen Juang; Chun-Tung Kuo; Ping-Hsueh Lee; Duan-Rung Chen (BMC Medical Ethics)
Abstract Background Taiwan passed the Patient Right to Autonomy Act in 2016 and introduced a legal document called advance decision to address dilemmas in making life-sustaining treatment (LST) decisions for incompetent patients. However, the proportion of Taiwanese adults who have completed an advance decision remains low, and public preference trends are unclear. Methods A cross-sectional telephone survey was conducted among Taiwanese adults using a structured questionnaire to assess preferences regarding five types of LSTs across four hypothetical clinical scenarios (late-stage motor neuron disease, severe dementia, irreversible coma, and terminal cancer). Participants were categorized based on their preference patterns, and factors associated with each subgroup were analyzed. Results Of the 3188 individuals contacted, 2440 declined to participate, and 748 (24.3%) respondents were successfully interviewed. A total of 747 responses were included in the analysis. Latent class analysis identified four preference subgroups: pro-forgo (more than half of the respondents), neutral, aggressive, and motor-neuron-disease specific. Older age, higher education, and better quality of life were associated with a greater likelihood of belonging to the pro-forgo group, while being male, unmarried, currently not working, or not residing in northern Taiwan were associated with a lower likelihood. Conclusions Most respondents expressed a consistent preference to forgo LSTs in the hypothetical clinical scenarios. This suggests that the advance decision, implemented in 2019, may align with public needs. However, given the low completion rate and prevalent preference patterns, policymakers should increase efforts to ensure that those in need have access to appropriate resources and consider implementing a tiered signing process.